2020
DOI: 10.1021/acs.jpcc.0c04396
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Laser Deposited Fe2TiO5 Photoanodes for Photoelectrochemical Water Oxidation

Abstract: Pulsed laser deposition (PLD) is an appealing technique to fabricate thin films with specific film orientation, stoichiometry, and morphology through tuning of experimental parameters. Here, we present Fe2TiO5, one of the promising photoanode materials, grown on fluorine-doped tin oxide (FTO) substrates through PLD. The structural and morphological properties of Fe 2 TiO 5 films, grown at room temperature and under varying oxygen pressure were studied. After deposition, all films were annealed in air at 650°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Their bandgap values of oxygen-deficient thin films are 2.18 eV (direct gap) and 2.04 eV (indirect gap). 46 If one compares the values of the bandgaps in the current study with those required for good photocatalysis, one finds that these values remain well within the range of the optimum bandgap of 1.6–2 eV, as pointed out by Bassi et al 46 Of significant note are the defect states in the minority channel of the Co-substituted sample (Fig. 9(d)), which decrease the bandgap significantly from that of the majority channel.…”
Section: Resultssupporting
confidence: 73%
“…Their bandgap values of oxygen-deficient thin films are 2.18 eV (direct gap) and 2.04 eV (indirect gap). 46 If one compares the values of the bandgaps in the current study with those required for good photocatalysis, one finds that these values remain well within the range of the optimum bandgap of 1.6–2 eV, as pointed out by Bassi et al 46 Of significant note are the defect states in the minority channel of the Co-substituted sample (Fig. 9(d)), which decrease the bandgap significantly from that of the majority channel.…”
Section: Resultssupporting
confidence: 73%
“…In contrast, Fe 2 TiO 5 , the mineral known as pseudobrookite with a band gap of 2.18 eV, does not have this issue due to its stoichiometry hosting the most stable oxidation states for both cations. Recently, this material has been incorporated in polycrystalline heterostructures, such as Fe 2 TiO 5 /α-Fe 2 O 3 or Fe 2 TiO 5 /TiO 2 nanostructures, and has been shown to greatly enhance the photoanodic performance. Several explanations have been proposed, such as favorable band edge positioning for bulk charge separation and reduced surface recombination; nevertheless, the nanostructured nature of the photoanodes, for example, with multiple crystal facets and variation in the size of each nanostructure, have limited the characterization of the intrinsic PEC properties. This calls for a well-defined surface to elucidate the underlying surface reaction mechanisms. Epitaxial thin films with well-defined crystalline orientation, surface flatness, surface area, and film thickness are ideal for such studies and serve as a solid platform for developing high-performance photoelectrodes, minimizing the effects from high-density grain boundaries or local off-stoichiometry commonly present in polycrystalline samples …”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Bassi et al . also reported for the first time Fe 2 TiO 5 photoanodes grown by pulsed laser deposition . Lee et al .…”
Section: Introductionmentioning
confidence: 93%
“…10 Very recently, Bassi et al also reported for the first time Fe2TiO5 photoanodes grown by pulsed laser deposition. 12 Lee et al reported a novel electrochemical method based on the use of metal-catechol complexes for the fabrication of pure Fe2TiO5 photoanodes. 13 Kuang et al reported an electrospray technique for the preparation of Fe2TiO5 photoanodes and posteriorly modified them by surface state passivation with Al 3+ and by FeOOH decoration, showing both approaches were effective in increasing the resulting photocurrent density values to 0.52 mA cm -2 at +1.23 VRHE.…”
Section: Introductionmentioning
confidence: 99%